Income tax and income tax evasion in selected countries - Kovinić Nikola (Ekonomija: teorija i praksa, 2023)
Profit tax is a direct tax paid by all countries in the world, and it holds a great importance because it represents a very important source of public revenue. Taxpayers fulfill their income tax obligations by submitting tax returns for specific periods. However, with the establishment of taxes, the issue of tax evasion arises, posing challenges to public service financing. This paper aims to examine the amount and collection methods of profit tax in the USA, European OECD countries, the Republic of Croatia, and the Republic of Serbia. Additionally, it highlights the adverse effects of tax avoidance by taxpayers in the examined countries. The paper employs exploratory and classification methods to identify current trends in income tax and the prevalence of tax evasion. The research reveals significant variations in profit tax rates among the analyzed countries and differences in its contribution to total tax revenue. Furthermore, all observed countries are making great efforts to suppress evasion, which causes great damage to the economy.